Magnetotransport and induced superconductivity in Bi based three‐dimensional topological insulators. Issue 1 (6th December 2012) - Veldhorst, M.; Snelder, M.; Hoek, M.; Molenaar, C. G.; Leusink, D. P.; Golubov, A. A.; Hilgenkamp, H.; Brinkman, A.
Abstract: The surface of a three‐dimensional (3D) topological insulator is conducting and the topologically nontrivial nature of the surface states is observed in experiments. It is the aim of this paper to review and analyze experimental observations with respect to the magnetotransport in Bi‐based 3D topological insulators, as well as the superconducting transport properties of hybrid structures consisting of superconductors and these topological insulators. The helical spin‐momentum coupling of the surface state electrons becomes visible in quantum corrections to the conductivity and magnetoresistance oscil‐lations. An analysis will be provided of the reported magnetoresistance, also in the presence of bulk conductivity shunts. Special attention is given to the large and linear magnetoresistance. Superconductivity can be induced in topological superconductors by means of the proximity effect. The induced supercurrents, Josephson effects and current–phase relations will be reviewed. These materials hold great potential in the field of spintronics and the route towards Majorana devices. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim) Abstract : Topological insulators bear great promise for fundamental phenomena and applications. Magnetotransport measurements show rich phenomena including weak antilocalisation, Shubnikov–de Haas oscillations and large linear magnetoresistance. Proximity‐induced superconductivity has resulted in gate‐tunable and ballistic supercurrents, unusual Fraunhofer patterns and superconducting quantum interferometer devices. Here, Veldhorst et al. review the current status of the field and discuss the experiments that have been carried out to discriminate topological surface states from trivial (bulk) states.